An examination of factors impacting forensic professionals working with people who have offended sexually, with a focus on polymorphic offenders - Hart, Georgia (2024)
The provision of therapeutic care that forensic professionals provide to people who have offended sexually, often exposes them to personal and professional challenges. It is recognised that this population are frequently stigmatised based on the nature and severity of their crimes, which often precipitate emotional reactions and perpetuate negative attitudes towards them. The thesis examined factors impacting forensic professionals working therapeutically with individuals who have offended sexually, with a focus on polymorphic offenders. This allowed for insights and observations to be made about a more complex and diverse type of offending behaviour. It also considered the role that attitudes towards this population have on therapeutic engagements, comparing attitudes expressed by wider society too. This allowed for greater reflection on the attitudinal differences between such groups, comparing forensic professionals and the general public.